Genetic and environmental influences on affiliation with deviant peers during adolescence and early adulthood - Garcia, Sarah E (Developmental psychology, 2014)
Adolescence and early adulthood is a time when peer groups become increasingly influential in the lives of young people. Youth exposed to deviant peers risk susceptibility to externalizing behaviors and related psychopathology. In addition to environmental correlates of deviant peer affiliation, a growing body of evidence suggests that affiliation with deviant peers is heritable. This study examined the magnitude of genetic and environmental influences on affiliation with deviant peers, changes in the relative importance of these factors, and which of these factors contribute to the stability of affiliation across this critical developmental period using a longitudinal twin study design that assessed same-sex twins (485 monozygotic pairs, 271 dizygotic pairs) at three discrete ages-15-, 18-, and 21-years-old. Biometric models revealed that genetic influences increased with age. New genetic influences appeared during late adolescence, and no new genetic influences emerged by age 21. Environmental influences shared by sibling pairs decreased with age, while the proportion of nonshared environmental effects unique to each individual remained relatively stable over the course of development. Shared environmental influences were largely age-overlapping whereas nonshared environmental influences were largely age-specific. In summary, this study found variance in affiliation with deviant peers is explained by shared and nonshared environment effects as well as by genetic influences (46% by age 21), supporting the role of genetically influenced selection factors. The shared environment was almost exclusively responsible for the stability in late adolescence, while genetic influences were primarily responsible for stability in early adulthood